2022
DOI: 10.1038/s41413-022-00207-y
|View full text |Cite
|
Sign up to set email alerts
|

Progress in osteoarthritis research by the National Natural Science Foundation of China

Abstract: Osteoarthritis (OA) in China is gradually becoming an important scientific research area that has had a significant impact on research and development (R&D) activities in the OA field worldwide. This article summarizes the R&D progress related to OA in China in recent years. The National Natural Science Foundation of China (NSFC) is a national funding institution for basic research and plays a critical role in promoting and supporting Chinese scholars’ R&D activities. We collected and analyzed info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…In general, radiographic OA is more prevalent than symptomatic OA. 11 , 12 The Global Burden of Disease (GBD) study showed that the global OA prevalence was about 300 million in 2017 and rapidly increased to 530 million in 2019. 13 , 14 The prevalence rate of OA has elevated by 9.3% from 1990 to 2017 and by 13.25% from 1990 to 2019.…”
Section: Prevalencementioning
confidence: 99%
“…In general, radiographic OA is more prevalent than symptomatic OA. 11 , 12 The Global Burden of Disease (GBD) study showed that the global OA prevalence was about 300 million in 2017 and rapidly increased to 530 million in 2019. 13 , 14 The prevalence rate of OA has elevated by 9.3% from 1990 to 2017 and by 13.25% from 1990 to 2019.…”
Section: Prevalencementioning
confidence: 99%
“…Osteoarthritis (OA) is the most common debilitating disease, a leading cause of disability, and is characterized by chronic pain and whole arthropathies such as articular cartilage damage, synovitis, subchondral bone remodeling and osteophyte formation. 1 3 The prevalence of OA is increasing steadily due to the aging population and worldwide obesity epidemic, which brings a great social burden and imposes a major challenge on public health. 4 6 It is estimated that 303 million adults in the world were affected, and in China, approximately 61.2 million people had OA in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…OA has a complex disease process associated with synovium, articular cartilage, subchondral bone, ligament, joint capsule and muscles around joints ( Huang et al, 2022 ). With the accelerating of population aging, the population suffering from OA has reached 200 million, which results in huge living obstacles and heavy economic burden to the society ( Li Y. et al, 2022 ; Zhao et al, 2022 ). Over the past decades, intra-articular injection of various stem cells has emerged as an advanced therapy to delay the pathological progress of OA.…”
Section: Introductionmentioning
confidence: 99%